Pengaruh Pengelolaan Sampah Organik Dengan Metode Maggot Terhadap Minat Kunjungan Wisatawan Dalam Berkunjung Ke Kampung Wisata Cokrodiningratan - Afif, Fuadi; Metti, Lusia Leka; Purnama, Ica; Rajusky, Yosafat; Hermawan, Hary (Journal of Tourism Sciences, Technology and Industry, 2025)
Sustainable tourism is increasingly becoming a global trend, where cleanliness and waste management play a crucial role in enhancing the attractiveness of tourist destinations. Kampung Wisata Cokrodiningratan has adopted an organic waste management method using maggots as an innovative solution to reduce waste while attracting tourists interested in the concepts of ecotourism and educational tourism. This study aims to analyze the impact of organic waste management using the maggot method on tourists' interest in visiting Kampung Wisata Cokrodiningratan. Additionally, this research seeks to identify the most influential factors contributing to the appeal of environmentally educational tourism. A quantitative approach was employed in this study, using a survey technique involving 50 tourist respondents. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, Cronbach’s Alpha reliability test, and Pearson correlation analysis to measure the relationship between maggot-based waste management and tourists' interest in visiting. The findings indicate that tourists' awareness of the maggot method has a positive correlation with their interest in visiting (r = 0.372, p < 0.01). Furthermore, the environmental impact of the maggot method has a significant relationship with tourism appeal (r = 0.500, p < 0.01), while the educational aspect of this method is the most dominant factor in increasing tourist interest (r = 0.523, p < 0.01). Organic waste management using the maggot method has been proven to be a contributing factor in enhancing tourism appeal in Kampung Wisata Cokrodiningratan. Tourists are more attracted to destinations that offer green tourism and educational tourism concepts. Therefore, marketing strategies focused on environmental education and interactive experiences should be strengthened to improve the competitiveness of this destination.